An Assessment of Environmental Impact of a Prominent Contributor in Coalmining Industry of India - TRIPATHI, KANCHAN LATA; SRIVASTAVA, MANOJ KUMAR (The journal of contemporary issues in business and government, 2021)
The mining industry plays a crucial role in supporting the economic development of nation, but on the darker side it has some undesirable impacts on environment. Being a heavy pollution causing industry and an energy supply industry, mining industry is the focus of environmental protection work. It is evident that despite the increase in Corporate Environmental Disclosure, there remains a substantial heterogeneity in terms of how corporations hold accountability for their environmental impacts. Therefore, to understand this heterogeneity in a better way, this study examines the perceived Environmental Accountability of the NCL, (a prominent contributor in coalmining industry of India), by evaluating its impact on environment from the perspective of different stakeholders.